National estimates of emergency department visits for medication-related self-harm: United States, 2016–2019. Issue 6 (3rd August 2022) - Geller, Andrew I; Ehlman, Daniel C; Lovegrove, Maribeth C; Budnitz, Daniel S
Abstract : Background: Medication poisoning is a common form of self-harm injury, and increases in injuries due to self-harm, including suicide attempts, have been reported over the last two decades. Methods: Cross-sectional (2016–2019) data from 60 emergency departments (EDs) participating in an active, nationally representative public health surveillance system were analysed and US national estimates of ED visits for medication-related self-harm injuries were calculated. Results: Based on 18 074 surveillance cases, there were an estimated 269 198 (95% CI 222 059 to 316 337) ED visits for medication-related self-harm injuries annually in 2016–2019 compared with 1 404 090 visits annually from therapeutic use of medications. Population rates of medication-related self-harm ED visits were highest among persons aged 11–19 years (58.5 (95% CI 45.0 to 72.0) per 10 000) and lowest among those aged ≥65 years (6.6 (95% CI 4.4 to 8.8) per 10 000). Among persons aged 11–19 years, the ED visit rate for females was four times that for males (95.4 (95% CI 74.2 to 116.7) vs 23.0 (95% CI 16.4 to 29.6) per 10 000). Medical or psychiatric admission was required for three-quarters (75.1%; 95% CI 70.0% to 80.2%) of visits. Concurrent use of alcohol or illicit substances was documented in 40.2% (95% CI 36.8% to 43.7%) of visits, and multiple medication products were implicated in 38.6% (95% CI 36.8% to 40.4%). The most frequently implicated medication categories varied by patient age. Conclusions: Medication-related self-harm injuries are an important contributor to the overall burden of ED visits and hospitalisations for medication-related harm, with the highest rates among adolescent and young adult females. These findings support continued prevention efforts targeting patients at risk of self-harm.